2008
DOI: 10.2319/010707-6.1
|View full text |Cite
|
Sign up to set email alerts
|

Bond Failure with a No-Mix Adhesive System

Abstract: For 1074 brackets bonded with a no-mix adhesive system in 63 patients, the mean time until first bracket failure was 235 days. The overall failure rate of brackets was 17.87%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…In our study we found no difference between the various Angle malocclusion types regarding the frequency of debonding incidences. However, in a previous prospective study on 63 patients, Bherwani et al 18 found significantly higher debonding incidences in class II division 2 malocclusions. The authors in that study, had not systematically investigated the bite type per debonding incidences, but it is noteworthy that class II division 2 patients often have a deep bite tendency which might be responsible for the higher failure rates observed, similar to what we found in our study.…”
Section: Discussionmentioning
confidence: 93%
“…In our study we found no difference between the various Angle malocclusion types regarding the frequency of debonding incidences. However, in a previous prospective study on 63 patients, Bherwani et al 18 found significantly higher debonding incidences in class II division 2 malocclusions. The authors in that study, had not systematically investigated the bite type per debonding incidences, but it is noteworthy that class II division 2 patients often have a deep bite tendency which might be responsible for the higher failure rates observed, similar to what we found in our study.…”
Section: Discussionmentioning
confidence: 93%
“…Success rates depend on the bonding agent employed, bonding tech nique used, etching time, concentration of the etch, or charac teristics of the bracket base. 1 Operator and patient factors are likely to influence the bond failure rate. Attention in the clinical technique, choice of proper bonding material, even slight contamination with saliva or lack of improper compositeprimer application can lead to weaker bond strength between enamel and bracket and these factors are controlled by the operator.…”
Section: Discussionmentioning
confidence: 99%
“…Gender and age of the patient, the presenting malocclusion, hard sticky diet during treatment, care taken of the appliance and generation of biofilm due to bad hygiene are patient variables. 1,3032 Bond failures involving the enamel to resin interface are undesirable clinically as the risk of enamel damage when debonding may be increased. Failures that occur at the bracket to resin interface are much preferable in this regard.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations